PEMANFAATAN Aspergillus japonicus PADA BEBERAPA JENIS MEDIA PERBANYAKAN TERHADAP PERTUMBUHAN BIBIT TANAMAN KAKAO (Theobroma cacao L.) - Hasmira Hasmira; Eka Wisdawati; Baso Darwisah (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2022)
ABSTRAK One way to increase the growth of cacao seedlings with use fungi to stimulate plant growth that can grow on media containing organic matter that is able to meet its nutrients. Therefore, this study aimed to determine the effect of several types of Aspergillus japonicus propagation media in increasing the growth of cocoa plants. This research was conducted at the Screen House, Department of Plantation Cultivation, Pangkep State Agricultural Polytechnic Campus. The experimental method used a Randomized Block Design (RAK) with 4 treatments, namely no treatment (soil), Aspergillus japonicus propagation on rice media, Aspergillus japonicus propagation on corn media, and Aspergillus japonicus propagation on husk media. The results showed that the growth of A. japonicus on husk media had a significant effect on the stem diameter parameters and the highest stem height observation was given the husk media, which was 19.8 cm.